Event Log Construction from Multimodel Data - A Reference Architecture for Exploiting Process Mining in IT Service Management - Reinhard, Philipp; Ließmann, Annina; Weinzierl, Sven; Zilker, Sandra; Li, Mahei M.; Matzner, Martin; Leimeister, Jan Marco (Proceedings of the 33rd European Conference on Information Systems, 2025)
Process mining holds substantial potential to discover and optimize processes utilizing event log data. However, current applications primarily rely on (semi-)structured data from process-aware information systems, limiting their capacity to incorporate multimodal data from diverse sources, particularly in domains like IT service management (ITSM). While existing stand-alone approaches can extract event log data from unstructured sources such as videos, documents, or bot logs, they fall short of leveraging the full range of real-world data available in ITSM. To address this gap, our research focuses on developing a reference architecture for constructing event logs from multimodal data. This architecture integrates diverse data types, construction functions, and process mining use cases. Following a design science research methodology, we aim to evaluate the architecture through a software artifact leveraging real-world ITSM data and incorporating state-of-the-art generative AI. In this study, we present the preliminary reference architecture and share early insights from expert evaluations.<br